1994
DOI: 10.1002/ajim.4700260506
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to lead, kidney function tests, and blood pressure

Abstract: In the present study we examined sensitive biochemical markers of kidney function and damage in 166 workers exposed to lead and in 60 control workers. The objective was to investigate the chronic renal toxicity of lead and its possible correlation with arterial pressure. Diastolic arterial pressure was higher in the exposed group (p < 0.05), but the two groups did not differ in systolic pressure. Median activity of urinary N-acetyl-beta-D-glucosaminidase was higher in the exposed group (p < 0.001), and correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 31 publications
3
25
1
Order By: Relevance
“…Hertz Picciotto [24] suggested a small positive association between blood lead and blood pressure in both occupational and general population. Dos Santos and Maheswaran [25,26] noted a significant correlation between systolic and diastolic blood pressure and duration of exposure to lead. These studies suggest that the blood pressure is correlated with Pb-B and Pb-U.…”
Section: Discussionmentioning
confidence: 98%
“…Hertz Picciotto [24] suggested a small positive association between blood lead and blood pressure in both occupational and general population. Dos Santos and Maheswaran [25,26] noted a significant correlation between systolic and diastolic blood pressure and duration of exposure to lead. These studies suggest that the blood pressure is correlated with Pb-B and Pb-U.…”
Section: Discussionmentioning
confidence: 98%
“…Two studies reported only on young children (Ͻ10 years), 25,37 two studies were case reports, 45,48 one 66 recruited less than 50 persons, in one 54 owing to missing information the analysis was performed in less than 50 subjects, five estimated exposure from other measurements than the blood lead concentration, 30,77,78,81,88 and 11 did not provide enough information to compute the association size. 17,19,22,26,27,36,39,62,63,67,86 …”
Section: Selection Of Studiesmentioning
confidence: 99%
“…They can be useful in early diagnose of acute renal damage as nephrotoxicity caused by immunosuppressive drugs, contrast substances, antibiotics and cadmium exposition (3)(4)(5)(6)(7)(8)(9)(10). Urinary enzyme activity normally is very low in urine and is increased in renal tubular cell damage (11).…”
Section: Introductionmentioning
confidence: 99%
“…Sensitive methods for determination of enzyme activities in urine. 3. High concentration of examined enzymes in renal tissue.…”
Section: Introductionmentioning
confidence: 99%